Volumetric oxygen transfer coefficient as fermentation control parameter to manipulate the production of either acetoin or D-2, 3-butanediol using bakery waste. (September 2021) - Maina, Sofia; Schneider, Roland; Alexandri, Maria; Papapostolou, Harris; Nychas, George-John; Koutinas, Apostolis; Venus, Joachim
Graphical abstract: Highlights: 2, 3-Butanediol and acetoin were efficiently produced using bakery waste hydrolysate. Volumetric oxygen transfer coefficient controls metabolic product formation. Bioprocess scale-up has been efficiently demonstrated at 50 L. High acetoin production efficiency has been achieved. Abstract: The formation of either acetoin or D-2, 3-butanediol (D-BDO) by Bacillus amyloliquefaciens cultivated on bakery waste hydrolysates has been evaluated in bioreactor cultures by varying the volumetric oxygen transfer coefficient ( kL a ). The highest D-BDO production (55.2 g L −1 ) was attained in batch fermentations with kL a value of 64 h −1 . Batch fermentations performed at 203 h −1 led to the highest productivity (2.16 g L −1 h −1 ) and acetoin production (47.4 g L −1 ). The utilization of bakery waste hydrolysate in fed-batch cultures conducted at kL a of 110 h −1 led to combined production of acetoin, meso-BDO and D-BDO (103.9 g L −1 ). Higher kL a value (200 h −1 ) resulted to 65.9 g L −1 acetoin with 1.57 g L −1 h −1 productivity. It has been demonstrated that the kL a value may divert the bacterial metabolism towards high acetoin or D-BDO production during fermentation carried out in crude bakery waste hydrolysates.